Values in Crisis Management - Hietaharju, Anssi (My University, 2012)
After the Cold War the number of different kinds of crises has increased in the world. The crises have also become more multidimensional, there are numerous different kinds of states, organizations and actors with different aims simultaneously involved. These factors have emphasized the significance of good management. In the modern day crises management crisis managers are often confronting unexpected and unforeseen situations for which they are not given any clear guidelines to lean on in their decisions or enough time in order to consider and examine their decisions profoundly. In these kinds of situations crisis managers have to use their own judgment and reasoning as a base of different decisions, and the main thing that is guiding managers’ decision making in these kinds of situations are values. This research has focused on the symbiosis of values and value management in crisis management. The aim of this research has been to find out what the values that the crisis managers hold important at their work are, whether values have significance for crisis managers and in what kind of situations do the crisis managers generally highlight their values. The theory part of this research deals with the concept of value, different groupings of values, values in an organization and value management. The empirical part of this research has been conducted with qualitative method. The empirical material has been gathered through interviews using a half-structured theme interview. The interview group consisted of fifteen Finnish crisis managers from different crisis management organizations. Based on the analysis of the empirical material we can conclude that crisis managers hold important a very wide variety of values. Regardless of this, three values stood out, management, accountability and sense of direction/ consistency, which can be interpreted to be important for all the crisis managers at their work. Values clearly have also significance for crisis managers in their management. Therefore, training that is focused more on values than it is today is seen desirable. However, crisis managers do not see that there should be some normative value recommendations for all the crisis managers but every manager should find, for example with the help of value training, their own important values. In addition, from the perspective of value management decision making situation seems to be the only situation that can be interpreted to be useful for all the crisis managers.
Keywords: KEY WORDS: values; value management; crisis; crisis management; crisis managers; fi=Julkisjohtaminen: European Civil Servants - kansainvälisen hallinnon ohjelma|en=Public Management: European Civil Servants|